2020
DOI: 10.1016/j.jacl.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Inclisiran—New hope in the management of lipid disorders?

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 59 publications
0
85
0
3
Order By: Relevance
“…Inclisiran sodium (inclisiran) is a short-chain, synthetic, small interfering ribonucleic acid (siRNA) that binds to PCSK9 messenger ribonucleic acid (mRNA) in hepatocytes, blocking PCSK9's translation and production [15]. Promising data from the ORION-1 phase II study, which demonstrated LDL-C lowering of > 50% with additional sustained pharmacodynamic effect and an ideal safety profile, led to the development of inclisiran's phase III ORION program [16,17].…”
Section: Inclisiran Molecule and Propertiesmentioning
confidence: 99%
“…Inclisiran sodium (inclisiran) is a short-chain, synthetic, small interfering ribonucleic acid (siRNA) that binds to PCSK9 messenger ribonucleic acid (mRNA) in hepatocytes, blocking PCSK9's translation and production [15]. Promising data from the ORION-1 phase II study, which demonstrated LDL-C lowering of > 50% with additional sustained pharmacodynamic effect and an ideal safety profile, led to the development of inclisiran's phase III ORION program [16,17].…”
Section: Inclisiran Molecule and Propertiesmentioning
confidence: 99%
“…Inclisiran (small interfering RNA molecule) acts with a completely new mechanism of inhibition of the PSCK9 protein in hepatocytes, targeting the messenger RNA for PCSK9 [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, with the advent of siRNA, researchers have designed a new generation of drugs to combat PCSK9 named Inclisiran. It can reduce the concentration of PCSK9 in the body by interfering PSCK9 gene expression in hepatocytes with a double-stranded short sequence of RNA, thereby reducing the degradation of LDLR and enhancing the ability of hepatocytes to eliminate LDL-C to reduce its levels ( Dyrbuś et al, 2020 ). In 2017, Ray et al (2017) found that Inclisiran could significantly reduce LDL-C after the first subcutaneous injection (>50%) and maintained this level for up to 1 year after the first injection.…”
Section: From Diagnosis Methods To Therapy Strategies Of Fh Based On mentioning
confidence: 99%